2016
DOI: 10.1097/md.0000000000002903
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitor Therapy Is Associated With Reduction of Early Bleeding Risk After Prophylactic Endoscopic Variceal Band Ligation

Abstract: Endoscopic variceal band ligation (EVL) is an effective procedure to control and prevent variceal bleeding in patients with liver cirrhosis, but it can be complicated by bleeding from post-EVL ulcers. Several studies have reported that proton pump inhibitors (PPIs) decrease the size of post-EVL ulcers. However, evidence are limited as to whether PPIs actually reduce the risk of bleeding after EVL. This study aimed to analyze the factors associated with bleeding after prophylactic EVL and to assess the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 26 publications
4
45
2
Order By: Relevance
“…However, a previous RCT suggested that the long‐term use of PPI reduced the risk of post‐EVL bleeding . A recent retrospective study also demonstrated that the lack of PPI administration was associated with bleeding after EVL . It was reported that gastroesophageal reflux occurred frequently in patients with portal hypertension and that acid suppression could help heal post‐EVL ulcers .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, a previous RCT suggested that the long‐term use of PPI reduced the risk of post‐EVL bleeding . A recent retrospective study also demonstrated that the lack of PPI administration was associated with bleeding after EVL . It was reported that gastroesophageal reflux occurred frequently in patients with portal hypertension and that acid suppression could help heal post‐EVL ulcers .…”
Section: Discussionsupporting
confidence: 93%
“…22 A recent retrospective study also demonstrated that the lack of PPI administration was associated with bleeding after EVL. 23 It was reported that gastroesophageal reflux occurred frequently in patients with portal hypertension and that acid suppression could help heal post-EVL ulcers. 24 In these studies, octreotide or PPI was administered from the first day after EVL when post-EVL ulcers had not formed.…”
Section: Discussionmentioning
confidence: 99%
“…7,15 Available evidence does not support a role of proton pump inhibitors for long-term prophylaxis of portal hypertension-related bleeding; however, the use of short-course proton pump inhibitor postendoscopic variceal ligation could reduce postbanding ligation ulcer size. 16 The use of an intravenous prokinetic agent (e.g., erythromycin) should be considered during the pre-endoscopy patient management phase. Barkun et al 17 reported that an intravenous infusion of different prokinetic agents administered up to 2 hours before endoscopy in patients with acute upper GI bleeding improved endoscopic visualization and significantly decreased the need for repeat endoscopy.…”
Section: Management Of the Acute Variceal Bleeding Episodementioning
confidence: 99%
“…This result is consistent with Shaheen et al [31] who found that pantoprazole reduces the size of post-banding ulcers after EVL. Also, Kang et al [32] concluded that non-use of PPI was independent risk factor for bleeding after prophylactic EVL (P= 0.002). On the other hand, Vanbiervliet et al [10] and Sinclair et al [27] found that PPI use was not associated with reduced risk of bleeding (P= 0.69 and 0.747 respectively).…”
Section: Discussionmentioning
confidence: 99%